Effects of metal-based additives on dehydrogenation process of 2NaBH4 + MgH2 system. (1st November 2022) - Shang, Yuanyuan; Jin, Ou; Puszkiel, Julián Atillio; Karimi, Fahim; Dansirima, Palmarin; Sittiwet, Chongsutthamani; Utke, Rapee; Soontaranon, Siriwat; Le, Thi Thu; Gizer, Gökhan; Szabó, Dorothée Vinga; Wagner, Stefan; et al.
Abstract: We report a systematic investigation of the effect that selected metal-based additives have on the dehydrogenation properties of the reactive hydride composite (RHC) model system 2NaBH4 +MgH2 . Compared to the pristine system, the material doped with 3TiCl3 ·AlCl3 exhibits superior dehydrogenation kinetics. The addition of 3TiCl3 ·AlCl3 alters the controlling mechanism of the second dehydrogenation step making it change from a two-dimensional interface controlled process to a two-dimensional nucleation and growth controlled process. The microstructural investigation of the dehydrogenated 2NaBH4 +MgH2 via high-resolution transmission electron microscopy (HRTEM) shows significant differences in the MgB2 morphology formed in the doped and undoped systems. The MgB2 has a needle-like structure in the sample doped with 3TiCl3 ·AlCl3, which is different from the plate-like MgB2 structure in the undoped sample. Moreover, nanostructured metal-based phases, such as TiB2 /AlB2 particles, acting as heterogeneous nucleation sites for MgB2 are also identified for the sample doped with 3TiCl3 ·AlCl3 . Highlights: Ti and Al-based additives strongly enhances the material dehydrogenation properties. The formed Ti and Al borides stronghly influence the microstructural features of MgB2 . Crystallographic-chemical theory of nucleation and growth is a potential tool to identify new additives.